Upper to lower limb coordination dynamics in swimming depending on swimming speed and aquatic environment manipulations - Guignard, B.; Rouard, A.; Chollet, D.; Bonifazi, M.; Dalla Vedova, D.; Hart, J.; Seifert, L. (Motor control, 2019)
Swimming is a challenging locomotion, involving the coordination of upper and lower limbs to propel the body forward in a highly resistive aquatic environment. During front crawl, freestyle stroke, alternating rotational motion of the upper limbs above and below the waterline, is coordinated with alternating lower limb pendulum actions. The aim of this study was to investigate the upper to lower limbs coordination dynamics of eight male elite front crawlers while increasing swimming speed and disturbing the aquatic environment (i.e., pool vs. flume). Upper to lower limb frequency ratios, coordination, coupling strength, and asymmetry were computed from data collected by inertial measurement units. Significant speed effect was observed, leading to transitions from 1:1 to 1:3 frequency ratios (1:3 overrepresented), whereas 1:2 frequency ratio was rarely used. Flume swimming led to a significant lower coupling strength at low speeds and higher asymmetries, especially at the highest speeds, probably related to the flume dynamic environment.